Analysis of miR-203a-3p/SOCS3-mediated induction of M2 macrophage polarization to promote diabetic wound healing based on epidermal stem cell-derived exosomes. (March 2023) - Yang, Hao; Xu, Hailin; Wang, Zhiyong; Li, Xiaohui; Wang, Peng; Cao, Xiaoling; Xu, Zhongye; Lv, Dongming; Rong, Yanchao; Chen, Miao; Tang, Bing; Hu, Zhicheng; et al.
Abstract: Background: The development of therapeutic strategies to improve wound healing in individual diabetic patients remains challenging. Stem cell-derived exosomes represent a promising nanomaterial, and microRNAs (miRNAs) can be isolated from them. It is important to identify the potential therapeutic role of specific miRNAs, given that miRNAs can play a therapeutic role. Methods: qPCR, flow cytometry, and western blotting were used to verify the effect of epidermal stem cell-derived exosomes (EpiSC-EXOs) on M2 macrophage polarization and SOCS3 expression. By screening key miRNAs targeting SOCS3 in EpiSC-EXOs by high-throughput sequencing, we verified the mechanism in vitro. Finally, an animal model was used to verify the effect of promoting healing. Results: The use of EpiSC-EXOs reduced SOCS3 expression and promoted M2 macrophage polarization. The abundant miR-203a-3p present in the EpiSC-EXOs specifically bound to SOCS3 and activated the JAK2/STAT3 signaling pathway to induce M2 macrophage polarization. Treatment of the db/db mouse wound model with miR-203a-3p agomir exerted a pro-healing effect. Conclusions: Our results demonstrated that the abundant miR-203a-3p present in EpiSC-EXOs can promote M2 macrophage polarization by downregulating SOCS3 and suggested that diabetic wounds can obtain better healing effects through this mechanism.